Analysis of the limiting factors for large scale microalgal cultivation: A promising future for renewable and sustainable biofuel industry. (December 2020) - Avinash, A.; Sasikumar, P.; Pugazhendhi, Arivalagan
Abstract: In recent times, microalgae are perceived as potential feedstocks for next generation biofuel production. However, their large scale cultivation and associated lipid recovery are confined by a number of factors. In this perspective, an endeavor has been made in this work to analyze the limiting factors for large scale microalgal cultivation by an analytical framework using interpretive structural modeling approach. The limiting factors were first identified through a comprehensive literature study and then, the interactions among the factors were formulated. Subsequently, the key factors that drive the system were identified by the multiplication properties of matrices principle. The results indicated that various operational and environmental factors would influence the mircroalgal culturing technology, the economy of fuel production and sustainability of the process. The study also showed that there were no autonomous and linkage factors indicating that no factors in this study with weak drive and weak dependence powers and all the factors considered were stable. Moreover, it was identified that the relevant policy mechanism with incentives and other supportive measures would benefit the growth of the algal biofuel industry. The present study can provide explicit information to support the growth of the sustainable biofuel industry. Graphical abstract: Image 1 Highlights: Microalgae as a potential feedstock for next generation biofuel production. Limiting factors in large scale microalgal cultivation examined. The limiting factors have a greater impact on the sustainability of the process. Implementation of relevant policy will benefit sustainable algal biofuel industry.